Peran Dewan Perwakilan Rakyat Daerah Dalam Pengawasan Pemerintah Daerah Kabupaten Manokwari Berdasarkan Undang – Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Irfan Christianto; Filep Wamafma; Atang Suryana (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research discusses the role of the Regional People's Representative Council (DPRD) in supervising Regional Government which has legislative, budget and supervisory functions. The tasks of the Regional People's Representative Council are normatively a reflection of democratic life in regional government. Law Number 23 of 2014 concerning Regional Government gives the Regional People's Representative Council (DPRD) a central role in supervising regional government. Through various provisions, this law mandates the DPRD to carry out various supervisory functions over regional government. The DPRD has a role in supervising general policy, budget implementation, government performance, drafting regional regulations, as well as being involved in the policy formation process. Apart from that, the DPRD also has special rights such as interpellation and inquiry rights to ensure transparency, accountability and public participation in supervision of regional government. This abstract summarizes the essence of the DPRD's role in supervising regional government in accordance with the Regional Government Law, which aims to maintain integrity, efficiency and community interests in the implementation of regional government.